Hubungan Sanitasi Lingkungan dengan Kejadian Stunting Anak Usia 2–5 Tahun - Sofia; Khairunnisa; Budi Arianto (Lembaga Teewan Journal Solutions, 2026)
Inadequate sanitation, such as the use of unhygienic toilets and open waste management, results in E. coli contamination of water sources and the surrounding area. Children living in such environments are at high risk of chronic diarrhea and impaired nutrient absorption, known as environmental enteropathy. If this situation persists throughout the first 1,000 days of life, stunted growth, or stunting, is a sure outcome. This study aimed to analyze the relationship between environmental sanitation and stunting in children aged 2–5 years at the Krueng Barona Jaya Community Health Center, Aceh Besar Regency, in 2025. The study used an analytical observational design with a case-control approach. A sample of 60 toddlers, consisting of 30 cases and 30 controls, was selected by age and gender matching. There was a significant association between access to clean water, waste management, and toilet use, and stunting. Inadequate environmental sanitation, clean water supply, inadequate waste management, and unhygienic toilet use collectively increase the risk of pathogen contamination and recurrent infections in children, ultimately hindering nutrient absorption and triggering stunting. Improve sanitation facilities and activate PHBS counseling, especially regarding the importance of washing hands with soap, drinking water treatment, and toilet maintenance.